Beyond conventional therapies: MSCs in the battle against nerve injury - Shuo Song; Cong Li; Ya Xiao; Ziyu Ye; Mingdeng Rong; Jincheng Zeng (Regenerative Therapy)
Nerve damage can cause abnormal motor and sensory consequences, including lifelong paralysis if not surgically restored. The yearly cost of healthcare in the United States is projected to be $150 billion, and millions of Americans suffer from peripheral nerve injuries as a result of severe traumas and disorders. For nerve injuries, the outcome of conventional therapies is suboptimal and may have unfavorable side effects. However, mesenchymal stem cells (MSCs) have been proven to be a viable option for the reconstruction of injured nerve tissue and bring a ray of hope. These stem cells are derived from bone marrow, adipose tissue, and human umbilical cord blood and have the ability to secrete trophic factors, contribute to the immune system, and stimulate axonal regeneration. The purpose of this review is to examine the potential benefits of MSCs for enhancing functional recovery and patient prognosis by highlighting their characteristics and elucidating their mechanism of action in nerve injury healing.